La invención del mundo en la obra de Victoria Iranzo - Suárez, Ventura Alejandro Pérez (2017)
The aim of this article is to focus the pictorial work of Victoria Iranzo, approaching from the cosmovision as a representation of the image of the world, the use of the model as an auxiliary element in her pictorial process and the metamap´s revision, in the quality of the worldview´s cartography, as a general theme of his work. This text concludes in a path of the history of the world’s image that concludes in her hypothesis and methodology: it is still possible the world’s invention from the combination of its given parts